Characterising the research profile of the critical care physiotherapy workforce and engagement with critical care research: a UK national survey. Issue 6 (4th June 2018) - Connolly, Bronwen; Allum, Laura; Shaw, Michelle; Pattison, Natalie; Dark, Paul
Abstract : Objective: To characterise the research profile of UK critical care physiotherapists including experience, training needs, and barriers and enablers to engagement in critical care research. 'Research' was defined broadly to encompass activities related to quantitative and qualitative studies, service evaluations, clinical audit and quality improvements. Design: Closed-question online survey, with optional free-text responses. Setting: UK critical care community. Participants: UK critical care physiotherapists, regardless of clinical grade or existing research experience. Results: 268 eligible survey responses were received during the 12-week study period (21 incomplete, 7.8%). Respondents were based in university-affiliated (n=133, 49.6%) and district general (n=111, 41.4%) hospitals, and generally of senior clinical grade. Nearly two-thirds had postgraduate qualifications at master's level or above (n=163, 60.8%). Seven had a doctoral-level qualification. Respondents reported a range of research experience, predominantly data acquisition (n=144, 53.7%) and protocol development (n=119, 44.4%). Perceived research training needs were prevalent, including topics of research methods, critical literature appraisal, protocol development and statistical analysis (each reported by ≥50% respondents). Multiple formats for delivery of future research training were identified. Major barriers to research engagement included lack of protected time (n=220, 82.1%), funding (n=177, 66.0%) and perceived experience (n=151, 56.3%). Barriers were conceptually categorised into capability, opportunity and motivation themes. Key enabling strategies centred on greater information provision about clinical research opportunities, access to research training, secondment roles and professional networks. Conclusions: UK critical care physiotherapists are skilled, experienced and motivated to participate in research, including pursuing defined academic research pathways. Nonetheless wide-ranging training needs and notable barriers preclude further involvement. Strategies to harness the unique skills of this profession to enhance the quality, quantity and scope of critical care research, benefiting from a multiprofessional National Clinical Research Network, are required.